Comparison of the pull-out force of different microtube-based methods in fractured endodontic instrument removal: An in-vitro study - Nasim Hashemi; Mohsen Aminsobhani; Mohammad Javad Kharazifard; Fatemeh Hamidzadeh; Pegah Sarraf (BMC Oral Health)
Abstract Background The fracture of an endodontic instrument within the root canal system can occur during root canal therapy, complicating thorough cleaning and shaping. Consequently, managing the broken fragment becomes crucial. Methods Eighty Nickel-titanium (NiTi) #20 K-files (Mani, Tochigi, Japan) were cut 8 mm from the tip, fixed into a corkboard, and classified into five groups (n = 14 each). The microtube-based methods included: microtube with cyanoacrylate glue (group 1), light-cured flowable composite resin (group 2), wire (group 3), internal shaft (group 4), and laser (group 5). Each method grasped the separated instrument's free end above the corkboard, and a pull-out test was performed using a universal testing machine(UTM). Additionally, 10 samples were separated in extracted canine root canals, and the temperature of the outer surface of the root was measured using the microtube and laser methods. Results Groups 1 and 4 exhibited significantly greater pull-out force compared to the other groups (p < 0.001). Groups 2 and 5 demonstrated significantly lower pull-out forces (p < 0.001). In Group 5, the temperature increase was 11 °C on the tube surface and 3 °C on the root surface. Conclusion All microtube-based techniques are effective for fractured instrument removal, with cyanoacrylate glue and laser methods being particularly suitable for cases that require higher force.